Rapid Weight Loss Practices in Grapplers Competing in Combat Sports - Ranisavljev, Marijana; Kuzmanovic, Jovan; Todorovic, Nikola; Roklicer, Roberto; Dokmanac, Milorad; Baic, Mario; Stajer, Valdemar; Ostojic, Sergej M.; Drid, Patrik (Frontiers in Physiology, 2022)
Background: Grappling is a wrestling style that combines different techniques such as freestyle wrestling, jiu-jitsu, judo, sambo, and others. As with other combat sports, it requires categorizing the athletes in weight classes, which leads to the use of certain methods to lose body weight in a short amount of time which poses a serious threat to athletes’ health and well-being. Therefore, the objective of this study was to investigate the most widespread rapid weight loss (RWL) methods and sources of influence used by grappling athletes. Methods: A total of 145 athletes took part in the study by voluntarily filling out a questionnaire regarding their weight loss techniques and methods. They were divided into two groups, male (27.7 ± 5.2 years, 1.76 ± 0.13 m, 82.1 ± 20 kg) and female (27.33 ± 6.3 years, 1.65 ± 0.08 m, 64.3 ± 10.4 kg), for further statistical analysis. After calculating descriptive statistics for all the variables, a t-test was conducted for gender differences in weight loss and weight regain, and a chi-square test measured the diversity in techniques and source of influence. Results: Out of 145 participants, 120 athletes (85.2%) reported engaging in rapid weight loss prior to weigh-in. Coaches (52.4% and 59%) and teammates (42.6% and 22.1%) seemed to be the most influential on their rapid weight-loss strategies, whereas physicians (17.1% and 17.9%) and parents (23.2% and 23.1%) were the least influential. A statistical difference between men and women (p=0.05) was found when teammates were a source of influence, (42,6% and 21.1%, respectively). Regarding the methods used, both groups practiced gradual dieting (85.4% and 79.5%) as the most prevalent, followed by increased exercise (79% and 66.6%) and sauna (78,7% and 66.6%). Moreover, men trained in plastic suits significantly more often than women (67.1% vs. 41%, p=0.01). Conclusions: Rapid weight loss is detrimental to athletes’ health and wellbeing. Hence, it is crucial to find and implement methods that will control and ultimately limit its use in combat sports. Physicians and nutritionists need to be closely linked with the staff, collaborate and supervise the weight cutting.